Nepal needs midwifery - Bogren, M; Bajracharya, U.; Berg, M; Erlandsson, K; Ireland, J; Simkhada, P; Van Teijlingen, Edwin (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9907 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 41-44